The Mechanical Properties and Durability of the PE-BFRP Hybrid-Fiber-Engineered Cementitious Composite (ECC) - Shasha Xu; Wei Li; Xuezhen Wang; Hongze Zhang; Ju Liu; Hui Jiang; Xuebin Wang; Hongke Ma; Jun Shi; Zhenyun Yu; Kuangyu Dai (Buildings)
This paper investigates the effects of the basalt-fiber-reinforced polymer (BFRP) and polyethylene (PE) hybrid fiber ratio on the mechanical properties and durability of engineered cementitious composites (ECC). First, four different PE-BFRP hybrid fiber ECC mixtures were systematically prepared by controlling the fiber volume ratio of PE and BFRP fibers. The workability and mechanical properties of the hybrid fiber ECC (HFECC) were then evaluated using flowability tests and multi-scale mechanical tests, including compressive strength, flexural strength, bending toughness, and tensile performance. After that, the durability of HFECC with different fiber ratios was comprehensively assessed through freeze–thaw cycle tests and rapid ion migration tests. Finally, the interface morphology of fibers within the matrix was observed using scanning electron microscopy (SEM). The results show that an appropriate hybrid of PE and BFRP fibers can synergistically enhance the crack resistance and toughness of ECC, improving its failure mode. The best performance in terms of flowability and mechanical properties was observed for the HFECC mixture with 1.30% PE fiber volume and 0.30% BFRP fiber volume. With the increase in BFRP fiber content, the freeze–thaw resistance and chloride ion erosion resistance of HFECC were gradually enhanced. This study provides experimental and theoretical support for the design and engineering application of high-performance hybrid fiber ECC materials.